Mycophenolate mofetil for interstitial lung disease in dermatomyositis - Morganroth, Pamela A. (2010)
OBJECTIVE: To report our experience using mycophenolate mofetil as first-line treatment for dermatomyositis-associated interstitial lung disease. METHODS: We examined the medical records of all 16 dermatomyositis patients with interstitial lung disease seen in our outpatient university hospital dermatology clinic between May 26, 2006 and May 25, 2009. In this retrospective case series, we describe the clinical course of the four patients with definitive evidence of interstitial lung disease on radiologic imaging who were treated with mycophenolate mofetil and had pulmonary data available to document their outcome. All patients also received prednisone. RESULTS: All three patients with at least one year of follow-up on mycophenolate mofetil experienced complete normalization of pulmonary function tests (including diffusing capacity for carbon monoxide) and resolution of dyspnea. They were also able to reduce their prednisone doses. The only patient with pre- and post-treatment chest computed tomography imaging had total resolution of her interstitial opacities. The patient with only five months of post-treatment follow-up experienced an improvement in diffusing capacity for carbon monoxide from 44 to 77% predicted but no change in dyspnea. CONCLUSION: These promising data indicate that mycophenolate mofetil may be a useful therapy for interstitial lung disease in dermatomyositis patients, but larger studies are needed to more definitively evaluate this medication’s role in therapy.